1993
DOI: 10.1111/j.1530-0277.1993.tb05671.x
|View full text |Cite
|
Sign up to set email alerts
|

Liver Transplantation for Alcoholic Liver Disease: Survival of Patients Transplanted with Alcoholic Hepatitis Plus Cirrhosis as Compared with Those with Cirrhosis Alone

Abstract: From January 1986 through December 1991, a total of 221 patients with alcoholic liver disease received liver transplantation. In 147 of these cases, complete pretransplant histopathologic, demographic, and laboratory data (minimum of CBC, AST, ALT, total bilirubin, albumin, and prothrombin time) were available for review. Forty-five (30%) of the 147 recipients had alcoholic hepatitis plus cirrhosis (AH), whereas 70% had cirrhosis (CIRR) alone. Age and sex were similar in the subgroups, but the patients with CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 41 publications
1
24
1
Order By: Relevance
“…Yates et al 49 and others [18][19][20]25,35,50 have questioned using the duration of abstinence (6 months or other intervals) to predict recidivism. Also, in this study, a period of abstinence of less than 6 months before evaluation did not independently predict the presence or absence of alcohol consumption after OLT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yates et al 49 and others [18][19][20]25,35,50 have questioned using the duration of abstinence (6 months or other intervals) to predict recidivism. Also, in this study, a period of abstinence of less than 6 months before evaluation did not independently predict the presence or absence of alcohol consumption after OLT.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with acute alcoholic hepatitis would be evaluated 3 to 6 months after the resolution of the alcoholic hepatitis. 25 Patients who underwent OLT and were documented to be consuming alcohol through monthly random alcohol testing were immediately placed in intensive rehabilitation programs. This treatment process included active intervention from psychiatric and social services in their local community, as well as from within our transplant center.…”
Section: Methodsmentioning
confidence: 99%
“…The methods used to assess alcohol use varied widely: 84% used patient interviews, 16% used questionnaires, 47% used blood and urine alcohol tests, and 21% used abnormal liver function test results as a surrogate marker of alcohol use (many assessed alcohol consumption in multiple ways). Eleven of the 37 studies reported their definition of alcohol relapse: 10 studies used "any alcohol use posttransplantation," 15,17,[19][20][21]27,33,[41][42][43]59,60,65,66,86 and 1 study used "clinically significant alcohol consumption," 79 which was not defined further in the published text.…”
Section: Assessment Of the Design Of The Included Studiesmentioning
confidence: 99%
“…The reasons for excluding studies are listed in Table 1 65,66 ; and Pittsburgh. 19,[87][88][89] This reduced to 68 the total number of included studies ( Table 2). Among the included studies, potentially overlapping data are presented from the following institutions: Birmingham, UK; King's College, UK; and multisite studies in France; Vienna, Austria; Virchow Clinic, Berlin, Germany; University of Colorado; University of Pittsburgh; Duke; and the University of Michigan.…”
Section: Identified Studiesmentioning
confidence: 99%
“…One other factor to support the immune system is seen in alcoholic patients who have received a liver transplant. If these individuals start consuming ethanol, hepatic fibrosis or cirrhosis occurs much more quickly than the years it took to develop prior to transplant [119] . This quick memory response to the liver suggests that the adaptive immune system is involved.…”
Section: Resultsmentioning
confidence: 99%